Computational analysis of heat shock proteins and ferroptosis-associated lncRNAs to predict prognosis in acute myeloid leukemia patients - Ge, Fangfang; Wang, Yulu; Sharma, Amit; Jaehde, Ulrich; Essler, Markus; Schmid, Matthias; Schmidt-Wolf, Ingo G. H. (Frontiers in Genetics, 2023)
Owing to their functional diversity in many cancers, long non-coding RNAs (lncRNAs) are receiving special attention. LncRNAs not only function as oncogenes or tumor suppressors by participating in various signaling pathways, but also serve as predictive markers for various types of cancer, including acute myeloid leukemia (AML). Considering this, we investigated lncRNAs that may act as a mediator between two processes heat shock proteins (HSPs) and ferroptosis, which appear to be closely related in tumorigenesis. Using a comprehensive bioinformatics approach, we identified four lncRNAs (AL138716.1, AC000120.1, AC004947.1, LINC01547) with prognostic value in AML patients. Of interest, two of them (AC000120.1 and LINC01547) have already been reported to be AML-related, and AC004947.1 is considered to have oncogenic potential. In particular, the signature obtained showed a lower survival probability with high-risk patients and vice versa. To our knowledge, this is the first predictive model of lncRNA that may correlate with the processes of HSPs and ferroptosis in AML. Nevertheless, validation using patient samples is warranted.